Comparison of FACTS device installation in power transmission system - Jumaat, S.A.; Musirin, I.; Othman, M.M.; Mokhlis, Hazlie (Praise Worthy Prize, 2012)
ABSTRACT Mechanism of power system operations become more complex due to the increasing load demand and which lead to increased pressure and high risk to the transmission line. Therefore power system operation and stability become less safe due to unexpected congestion and voltage violations. In additional, new transmission line is considered one of the solutions to provide a stable operation it is more secure to the power system. However it is more expensive and time consuming which also need to address the political and environmental issues. One of the alternatives which can be employed is the use of Flexible AC Transmission System (FACTS). This paper presents a study on optimal location and sizing of FACTS device based on Particle Swarm Optimization for minimization of transmission losses, voltage profile improvement which takes into account cost of installation. In this study, Static Var Compensator (SVC) and Thyristor Controlled Series Compensator (TCSC) are chosen as the compensation device. Validation through the implementation on the IEEE 30-bus system indicated that PSO is feasible to achieve the task. In simulation results are compared with those obtained from Evolutionary Programming (EP) and Artificial Immune System (AIS) technique in the attempt to highlight its merit.